Maize grain and soil surveys reveal suboptimal dietary selenium intake is widespread in Malawi - Chilimba, Allan D. C.; Young, Scott D.; Black, Colin R.; Rogerson, Katie B.; Ander, E. Louise; Watts, Michael J.; Lammel, Joachim; Broadley, Martin R. (Nature Publishing Group, 2011)
Selenium is an essential element in human diets but the risk of suboptimal intake increases where food choices are narrow. Here we show that suboptimal dietary intake (i.e. 20–30 mg Se person21 d21) is widespread in Malawi, based on a spatial integration of Se concentrations of maize (Zea mays L.) grain and soil surveys for 88 field sites, representing 10 primary soil types and .75% of the national land area. The median maize grain Se concentration was 0.019 mg kg21 (range 0.005–0.533), a mean intake of 6.7 mg Se person21 d21 from maize flour based on national consumption patterns. Maize grain Se concentration was up to 10-fold higher in crops grown on soils with naturally high pH (.6.5) (Eutric Vertisols). Under these less acidic conditions, Se becomes considerably more available to plants due to the greater solubility of Se(IV) species and oxidation to Se(VI).